Between Lévinas and Arendt – Philosophical Origins of Alain Finkielkraut’s Reflection on the Other and the Education - Liszka, Katarzyna; Włodarczyk, Rafał (Journal of Education Culture and Society, 2020)
A member of the generation of student revolt ’68, Alain Finkielkraut is thought to be one of the most prominent intellectuals in France, taking part in public debates on several issues essential for Europe and the world. His assays, articles and books may be read as a complex commentary with a sound humanistic background to the condition of western culture as well as to current socio-political events. Our article focuses on revealing theoretical grounding of Finkielkraut’s reflection in the philosophies of Emmanuel Lévinas and Hannah Arendt. We attempt to reconstruct the way Finkielkraut employs his critical apparatus built on their thought to the field of educational practices in order to present the specific perspective of educational research and to contribute to the knowledge produced by widely understood critical pedagogic.